The Determinants of Islamic Bank Performance: An Assessment of Jaiz Bank Plc Nigeria - Aminu Abdullahi; Yahaya Yusuf (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The paper assessed whether the bank-specific factors (internal) and economic (external factors) determine the financial performance of Jaiz bank Nigeria as an Islamic bank. Secondary data from the bank’s financial statements and world banks Development indicators were extracted for the period of 8 years (2011 to 2018). After description analysis, OLS regression was utilized to determine the effect of independent variables (GDP, Inflation, Interest, capital adequacy, credit risk, deposit ratio, and cost efficiency) have on the dependent variables (ROA, ROE, and ROI) financial performance. It was established that; GDP as an external factor has a significant positive association with financial performance, cost efficiency was discovered to have a weak positive relationship with the financial performance, while inflation rate, interest rate, capital adequacy, deposit ratio, and credit risk were found to have no significant effect on the bank’s financial performance. It was recommended that; Islamic banks need to give more consideration to the economic factors in their policies and programs as they may influence their profitability. More studies are also needed to compare the determinants of Islamic banks with that of Money Deposit Banks.